The Performance Analysis and Monitoring of Grid-connected Photovoltaic Power Plant - Esmaeilion, Farbod; Ahmadi, Abolfazl; Esmaeilion, Aryan; Ehyaei, Mehdi Ali (Current Chinese Computer Science, 2021)
Objectives: The purpose of this study is to analyze the performance of a one-megawatt photovoltaic power plant in Arak-Iran, according to IEC-61724 standard, using data recorded over a year. The photovoltaic plant of Arak is located at coordinates 34.0954° N and 49.7013° E. This power plant is the first-megawatt photovoltaic power plant in Iran which two types of modules are used and it was constructed by the New Energy Agency and the Power Research Center under the supervision of the Ministry of Energy in 2016. In this plant, a combination of monocrystal and polycrystalline modules is used, and the annual output is 1756 MWh. Methods: The combination of modules is based on the 1920 modules of 250 W of polycrystalline and 260 modules of 260 W of monocrystal in the construction of the power plant. There are also 4 inverters and a 1250 KVA dry power trans-former. The plant has suitable productivity, with a performance ratio equal to 0.8 and a final yield of 4.57. Results and Conclusion: Ultimately the PV plant is simulated by PVsyst and the results are compared with monitored records which indi-cated the appropriate accuracy of the collected data. The calculated performance ratio for the power plant by PVsyst is 81.2% and has a 1.5% difference with the monitored totals. The energy supplied during one year by the power plant is 1756 MWh, whereas the prediction of annual energy yield that entered to the grid is equal to 1757 MWh.
Keywords: Grid-connected